PENGARUH LIKUIDITAS, FINANCIAL LEVERAGE, AKTIVITAS TERHADAP RETURN SAHAM DENGAN PROFITABILITAS SEBAGAI VARIABEL MEDIASI - Teddy Kurniawan; Yuliani .; Reza Ghasarma (Program Studi Magister Manajemen FE Unsri, 2016)
This research aims to analyze direct and indirect effect about liquidity, financial leverage and activities on stock return and with the mediation of ROA as a proxy of profitability ratio. The population were all company in Sub Sector of Automotive and Components are 12 companies. Purposive sampling used as the sampling technique and acquired 11 firms. The period in 2000-2013, unit of analysis is panel data with 154 observations. The data analysis method used is Path Analysis. The result shows that direct effect Current Ratio (CR) and Debt to Equity Ratio (DER) not have signed on Stock Return, while Total Asset Turnover (TAT) has a significant effect on Stock Return. The indirect effect the rule of ROA as full mediation in CR to stock return and as partial mediation in TAT to stock return. But not found the rule of ROA as mediation effect DER to stock return.